Multi-institutional Study of Otolaryngology Resident Intraoperative Experiences for Key Indicator Procedures. (August 2022) - Chen, Jenny X.; Deng, Francis; Filimonov, Andrey; Shuman, Elizabeth A.; Marchiano, Emily; George, Brian C.; Thorne, Marc; Pletcher, Steven D.; Platt, Michael; Teng, Marita S.; Kozin, Elliott D.; Gray, Stacey T.
Objective: There is concern that current otolaryngology residents may not receive adequate surgical training. We aimed to characterize residents' surgical experiences at 5 academic centers performing the 14 key indicator procedures (KIPs) outlined by the Accreditation Council for Graduate Medical Education. Study Design: Prospective study. Setting: Five otolaryngology training programs. Methods: Data were gathered from December 2019 to December 2020 with a smartphone application from the Society for Improving Medical Professional Learning. After each operation, residents and faculty rated trainee autonomy on a 4-level Zwisch scale and performance on a 5-level modified Dreyfus scale. Results: Residents and attendings (n = 92 and 78, respectively) logged 2984 evaluations. Attending ratings of resident autonomy and performance increased with training level ( P < .001). Resident self-assessments of autonomy and performance were lower than paired attending assessments ( P < .001). Among attending evaluations of KIPs performed by senior residents (postgraduate year 4 or 5), 55% of cases were performed with meaningful autonomy (passive help or supervision only). Similarly, attendings rated 55% of these cases as a practice-ready or exceptional performance. Senior residents had meaningful autonomy for ≥50% of cases for most KIPs, with the exception of flaps and grafts (40%), pediatric/adult airway (39%), and stapedectomy/ossiculoplasty (33%). Similarly, senior residents received practice-ready or exceptional performance ratings for ≥50% of cases across all KIPs other than pediatric/adult airway (42%) and stapedectomy/ossiculoplasty (33%). Conclusion: In this multicenter study, resident surgical autonomy and performance varied across otolaryngology KIPs. The development of nationwide benchmarks will help programs and residents set educational goals. Level of evidence: 2.